Reseña de: De la Escosura Balbás, María Cristina – Duce Pastor, Elena – González Gutiérrez, Patricia – Rodríguez Alcocer, María del Mar – Serrano Lozano, David (eds.): Blame it on the Gender. Identities and transgressions in Antiquit - Iriarte Asarta, Unai (Espacio Tiempo y Forma. Serie II, Historia Antigua, 2021)
Reseña de: De la Escosura Balbás, María Cristina – Duce Pastor, Elena – González Gutiérrez, Patricia – Rodríguez Alcocer, María del Mar – Serrano Lozano, David (eds.): Blame it on the Gender. Identities and transgressions in Antiquity, Oxford, BAR Publishing, 2020, 107pp., ISBN: 978-1-4073-5734-8.